Effects of sex hormones on brain GABA and glutamate levels in a cis- and transgender cohort. (April 2022) - Spurny-Dworak, B.; Handschuh, P.; Spies, M.; Kaufmann, U.; Seiger, R.; Klöbl, M.; Konadu, M.E.; Reed, M.B.; Ritter, V.; Baldinger-Melich, P.; Bogner, W.; Kranz, G.S.; et al.
Abstract: Sex hormones affect the GABAergic and glutamatergic neurotransmitter system as demonstrated in animal studies. However, human research has mostly been correlational in nature. Here, we aimed at substantiating causal interpretations of the interaction between sex hormones and neurotransmitter function by using magnetic resonance spectroscopy imaging (MRSI) to study the effect of gender-affirming hormone treatment (GHT) in transgender individuals. Fifteen trans men (TM) with a DSM-5 diagnosis of gender dysphoria, undergoing GHT, and 15 age-matched cisgender women (CW), receiving no therapy, underwent MRSI before and after at least 12 weeks. Additionally, sex differences in neurotransmitter levels were evaluated in an independent sample of 80 cisgender men and 79 cisgender women. Mean GABA+ (combination of GABA and macromolecules) and Glx (combination of glutamate and glutamine) ratios to total creatine (GABA+/tCr, Glx/tCr) were calculated in five predefined regions-of-interest (hippocampus, insula, pallidum, putamen and thalamus). Linear mixed models analysis revealed a significant measurement by gender identity effect (pcorr. = 0.048) for GABA+/tCr ratios in the hippocampus, with the TM cohort showing decreased GABA+/tCr levels after GHT compared to CW. Moreover, analysis of covariance showed a significant sex difference in insula GABA+/tCr ratios (pcorr. = 0.049), indicating elevated GABA levels in cisgender women compared to cisgender men. Our study demonstrates GHT treatment-induced GABA+/tCr reductions in the hippocampus, indicating hormone receptor activation on GABAergic cells and testosterone-induced neuroplastic processes within the hippocampus. Moreover, elevated GABA levels in the female compared to the male insula highlight the importance of including sex as factor in future MRS studies. Data availability statement: Due to data protection laws processed data is available from the authors upon reasonable request. Please contact rupert.lanzenberger@meduniwien.ac.at with any questions or requests. Highlights: Our analysis revealed a significant measurement by gender identity effect for hippocampal GABA+/tCr ratios after gender-affirming hormone therapy in trans men. Gender-affirming hormone therapy decreases hippocampal GABA+/tCr levels in trans men compared to cisgender women. GABA levels in the insula differ significantly between cisgender men and women assessed in a cohort of 159 individuals.